LIFE CYCLE ASSESSMENT OF PLASTIC PACKAGING PRODUCTION - Larasati, Kinanti; Frimawaty, Evi; Chairani, Ellyna (Journal of Environmental Science and Sustainable Development, 2024)
The plastic packaging industry has become a significant commodity that penetrates almost every aspect of our lives, requiring greater responsibility from the industry for the life cycle management of their products. Several study methodologies are available to measure the industry's environmental impact, with life cycle analysis (LCA) gaining traction in Indonesia. Therefore, this study aims to measure the environmental impact of the plastic packaging industry analyzed using LCA with a focus on the main potential impact categories of global warming, acidification of the earth, toxicity to humans, formation of photochemical oxidants, and fossil depletion, within the scope of cradle to gate which was analyzed using SimaPro software. This research compares with previous research conducted in several countries (such as Poland, Qatar, and France) that conducted LCA on the plastic packaging industry. The results from Bogor, West Java, Indonesia, showed that the increase in the amount of plastic packaging produced contributes to environmental impact. Comparative studies reveal that the environmental impact is influenced by factors such as the quantity of recycled materials, the number of circularity cycles, and waste management strategies. Future LCA studies should also aim to refine inventory data, delving into greater detail for each unit of the process. This will yield more precise insights into the overall environmental impact of the process.